Manifest Destiny and the journey west - Henzel, Cynthia Kennedy, 1954- (Expansion of our nation., 2019)
Describes the expansion of the United States westward, focusing on the Lewis and Clark expedition, the idea of Manifest Destiny, the Oregon Trail, and the removal of Native Americans. Also explores the role the Gold Rush played in the expansion West. Includes a quiz with answer key, a glossary, color illustrations, and further resources.